Analysis of the Relation Between the Number of Employees and Their Net Wages - Perić, Teodor; Jurić, Ivica; Vojnović, Savo (Promet - Traffic&Transportation, 2012)
The main task of this work is that of applying somespecific statistical and mathematical methods in researchingthe measures of concentration of the numberof employees and their net wages, in other words the incomesin certain economic branches of production andthe service sector in the Republic of Croatia.We deal here with the measures of inequality andevenness, and these are the Lorenz curve and the index ofconcentration. For the purpose of this research, 13branches, both from production and from the servicesectors, have been chosen for examining the measures ofconcentration according to the indicators.Before concrete realisation and calculation of thesemeasures of concentration can take place, a preliminaryvery delicate sorting out and modelling of the relevant parametershad to be carried out. This refers especially toadequate compounding of the carriers of the researchedphenomena.